Analisis Instagram Sebagai Media Promosi Desa Wisata Lebakmuncang - Suryadi, Kinanti Aulia (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
This study investigates the use of Instagram in promoting Lebakmuncang Tourism Village as a tourism destination. Using descriptive qualitative methods, an analysis was conducted on the Instagram account @desawisatalebakmuncang to evaluate the frequency of posting, content quality, hashtag usage, and level of interaction with followers. The results of the analysis indicate that this tourism village has great potential but requires improved marketing strategies through social media. Recommendations include increasing the frequency of posting, creating interactive content, and designing more varied campaigns. It is hoped that these improvements can optimize the role of Instagram in increasing the visibility, interaction, and attractiveness of Lebakmuncang Tourism Village as an attractive tourist destination.